Mengenal Budaya Betawi dalam Pembelajaran Sekolah Dasar : Observasi di SDN Karangantu untuk Meningkatkan Kesadaran Budaya Siswa - Ratna Dewi; Agus Ikhsan Farhan; Nuraliyah Nuraliyah; Sabrinah Meilani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to examine the implementation of Betawi cultural education in elementary school learning at SDN Karangantu to enhance students' cultural awareness. Using qualitative descriptive methods through observation, interviews, and documentation, this study investigates how Betawi cultural elements are integrated into the curriculum and their impact on students' understanding of local heritage. The research was conducted over three months involving 120 students from grades 1-6 and 8 teachers. Findings reveal that incorporating Betawi cultural elements such as traditional songs, folklore, and arts significantly improves students' cultural appreciation and identity formation. The study recommends systematic integration of local cultural content in elementary education curricula to preserve cultural heritage while enhancing educational quality.